Advanced biofabrication strategies for biomimetic composite scaffolds to regenerate ligament‐bone interface. Issue 4 (13th August 2021) - Jiang, Nan; Mao, Mao; Li, Xiao; Zhang, Weijie; He, Jiankang; Li, Dichen
Abstract: The natural ligament–bone interface features gradient changes in matrix composition, architecture and cell phenotype, which play critical roles in reliable ligament fixation and smooth loading transfer. Mimicking such organisations in artificial composite tissue‐engineering scaffolds is important for realising functional fixation between ligament implants and host bones. Here, the authors aim to provide a comprehensive review on the latest strategies to fabricate biomimetic composite scaffolds for the regeneration of ligament‐to‐bone interface. The biomimetic composite scaffolds are divided into stratified and gradient scaffolds, which are characterised as layer‐specific and continuous changes, respectively, in scaffold materials and/or microstructures. Biofabrication strategies for different types of composite scaffolds are summarised. The effects of material/structural changes on cellular morphology, cell differentiation, in vivo osteointegration and multi‐tissue interface regeneration are highlighted. Finally, the potential challenges and future perspectives in engineering biomimetic composite scaffolds for ligament–bone interface regeneration are discussed.